Chemical and biological study of the plant species Tithonia diversifolia - Miranda, Giulia Stavrakas; Rosa, Ana Carla Rangel; Andrade, João Victor; Nunes, Lara Pinheiro; Macedo, Adriely Valerio de; Verly, Leonardo Bindelli; Marques, Cecília Fernandes Patta Muller; Macedo , Maria Eduarda Dan; Couto, Joice Olinda do; Perin, Isabelle Lucas Braga; Santos, Mario Ferreira Conceição (Seven Editora, 2024)
With the advance of agriculture and the growing need for ways to control plagues, the large-scale use of synthetic herbicides has been causing some problems, such as soil pollution by persistent herbicide molecules, causing the emergence of resistant weed populations to control methods. Therefore, a lot of studies has been done aiming to find new compounds less toxic and persistent on the environment. The vegetable species Tithonia diversifolia is widely known for its invasive behavior. It is a plant native to Central America that spread across South and North America and across the world as an ornamental plant. A lot of reports on literature discourse about its alelopatic effect on many plant species, causing inhibition of growing and germination of seeds. Such effects are associated to sesquiterpene lactones, characteristic secondary metabolites from Asteraceae family, in which T. diversifolia belongs. In the present work, the extract of leaf washing of T. diversifolia using dichloromethane as solvent, from which the majoritarian compound was isolated and identified. The crude extract of leaf washing was submitted to in vitro phytotoxicity essay with Lactuca sativa seeds. The majoritarian compound was isolated though fractionation of the crude extract on silica flash column followed by a series of dilutions of fractions 1 and 2, and identified though nuclear magnetic resonance as being Tagitinin C. The signals of hydrogen and carbon were confirmed by comparison with data found on the literature. It was obtained a yield of 47,26% from the crude extract. The phytotoxicity essay with the crude extract of leaf washing reduced the growth of seedlings of L. sativa, however, exhibit less activity when compared with the herbicide Flumyzin®. DOI:https://doi.org/10.56238/sevened2023.001-010